A Comparison of Facial Proportions in Pleasing and Unpleasing Smile Photographs from Nepalese Population - Basnet, Bishal Babu (Journal of Nepalese Prosthodontic Society, 2019)
Introduction: Facial proportion and dental proportions are matters of interest for dental professionals to craft a beautiful smile. In facial analyses, the role of different proportions cannot be overlooked when planning dento facial treatment. This study aims to determine the different facial proportions; smile index, lower smile index, nose width to outer inter commissural width, intercanine width to outerinter commissural width, nose width to intercanine width and outer intercommissural width to lower facial height in esthetically pleasing smile (ES) and esthetically unpleasing smile (US) groups.Materials and methods: The frontal smiling photographs (N=152, 74 pleasing and 78 unpleasing smile) were gathered and different linear measurements were carried out using digital ruler. The facial proportions were derived and comparisons were made amongst groups and differences were examined in comparison to standard accepted proportion (such as Golden proportion).Results: Average smile index of ES (5.899±1.201) was lower than that of US group (6.421±1.675).The golden proportion was not valid for smile indices in each group. Mean nose width to intercanine width ratio significantly differed in ES and US. The outer inter commissural width to lower facial height was not statistically significantly different from 1:1 ratio.Conclusion: Most facial proportions in pleasing and unpleasing smiles showed no difference. The outer intercommissural width to lower facial height was found in 1:1 proportion current study with possible utilization in determining vertical dimension of occlusion.